2015
DOI: 10.1332/204674314x14018716992515
|View full text |Cite
|
Sign up to set email alerts
|

Parents’ involvement and university students’ independence

Abstract: Living away from home at university has long been seen as a first step on the road to fully independent living, but considerable concern has been expressed by some commentators that involved parenting – sometimes termed ‘helicopter parenting’ – threatens the transition to independence. We approached students and parents at two pre-1992 universities and interviewed 29 parent-student dyads. The paper focuses on non-financial support and the analysis takes the parents’ standpoint. Four categories of parental invo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 25 publications
(33 reference statements)
0
5
0
Order By: Relevance
“…The Federation of Student Islamic Societies says there are over 300,000 Muslim students in higher education in the UK (FOSIS, 2016). The university setting also provides students with new experiences and transition to independence (Lewis et al , 2015). The eating environment and food environment will be different, as consumers within a university setting are exposed to different social interactions, choices of food, cafes/refectories and situational factors (Meiselman, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The Federation of Student Islamic Societies says there are over 300,000 Muslim students in higher education in the UK (FOSIS, 2016). The university setting also provides students with new experiences and transition to independence (Lewis et al , 2015). The eating environment and food environment will be different, as consumers within a university setting are exposed to different social interactions, choices of food, cafes/refectories and situational factors (Meiselman, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…In the 2019/2020 academic year, there were over 1,204 million students, including the CSWU -9332, the WMU -6324 and the UL -24829 (GUS 2019). Students in Poland often choose a university in their hometown, while in other countries, such as the United Kingdom, students most often leave the parental home and move to a university residence (Lewis et al 2014). In this study, the highest percentage of students living with their parents was recorded in UL.…”
Section: Discussionmentioning
confidence: 56%
“…About one-tenth of the respondents in this study indicated that they missed their freedom away from parents, something which they enjoy when they are in school. Going to university has usually been associated with some level of freedom and independence (Lewis et al, 2015). Such autonomy and ability to independently make decisions are usually missed when students are in the midst of their parents and siblings.…”
Section: Discussionmentioning
confidence: 99%